a(a(a(x1))) → a(b(b(b(x1))))
b(b(a(b(x1)))) → a(a(a(x1)))
↳ QTRS
↳ DependencyPairsProof
↳ QTRS Reverse
↳ QTRS Reverse
a(a(a(x1))) → a(b(b(b(x1))))
b(b(a(b(x1)))) → a(a(a(x1)))
A(a(a(x1))) → B(x1)
B(b(a(b(x1)))) → A(x1)
A(a(a(x1))) → A(b(b(b(x1))))
B(b(a(b(x1)))) → A(a(x1))
A(a(a(x1))) → B(b(x1))
B(b(a(b(x1)))) → A(a(a(x1)))
A(a(a(x1))) → B(b(b(x1)))
a(a(a(x1))) → a(b(b(b(x1))))
b(b(a(b(x1)))) → a(a(a(x1)))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ QDPOrderProof
↳ QTRS Reverse
↳ QTRS Reverse
A(a(a(x1))) → B(x1)
B(b(a(b(x1)))) → A(x1)
A(a(a(x1))) → A(b(b(b(x1))))
B(b(a(b(x1)))) → A(a(x1))
A(a(a(x1))) → B(b(x1))
B(b(a(b(x1)))) → A(a(a(x1)))
A(a(a(x1))) → B(b(b(x1)))
a(a(a(x1))) → a(b(b(b(x1))))
b(b(a(b(x1)))) → a(a(a(x1)))
The following pairs can be oriented strictly and are deleted.
The remaining pairs can at least be oriented weakly.
A(a(a(x1))) → B(x1)
B(b(a(b(x1)))) → A(x1)
B(b(a(b(x1)))) → A(a(x1))
A(a(a(x1))) → B(b(x1))
B(b(a(b(x1)))) → A(a(a(x1)))
A(a(a(x1))) → B(b(b(x1)))
Used ordering: Polynomial interpretation [25,35]:
A(a(a(x1))) → A(b(b(b(x1))))
The value of delta used in the strict ordering is 3.
POL(B(x1)) = (3)x_1
POL(a(x1)) = 3 + x_1
POL(A(x1)) = (3)x_1
POL(b(x1)) = 2 + x_1
a(a(a(x1))) → a(b(b(b(x1))))
b(b(a(b(x1)))) → a(a(a(x1)))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ Narrowing
↳ QTRS Reverse
↳ QTRS Reverse
A(a(a(x1))) → A(b(b(b(x1))))
a(a(a(x1))) → a(b(b(b(x1))))
b(b(a(b(x1)))) → a(a(a(x1)))
A(a(a(a(b(x0))))) → A(b(a(a(a(x0)))))
A(a(a(b(a(b(x0)))))) → A(b(b(a(a(a(x0))))))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ Narrowing
↳ QDP
↳ SemLabProof
↳ SemLabProof2
↳ QTRS Reverse
↳ QTRS Reverse
A(a(a(a(b(x0))))) → A(b(a(a(a(x0)))))
A(a(a(b(a(b(x0)))))) → A(b(b(a(a(a(x0))))))
a(a(a(x1))) → a(b(b(b(x1))))
b(b(a(b(x1)))) → a(a(a(x1)))
A.0(a.0(a.1(b.0(a.1(b.0(x0)))))) → A.0(b.1(b.0(a.0(a.0(a.0(x0))))))
A.0(a.0(a.0(a.1(b.1(x0))))) → A.0(b.0(a.0(a.0(a.1(x0)))))
A.0(a.0(a.1(b.0(a.1(b.0(x0)))))) → A.1(b.1(b.0(a.0(a.0(a.0(x0))))))
A.0(a.0(a.0(a.1(b.1(x0))))) → A.1(b.0(a.0(a.0(a.1(x0)))))
A.0(a.0(a.1(b.0(a.1(b.1(x0)))))) → A.1(b.1(b.0(a.0(a.0(a.1(x0))))))
A.0(a.0(a.1(b.0(a.1(b.1(x0)))))) → A.0(b.1(b.0(a.0(a.0(a.1(x0))))))
A.0(a.0(a.0(a.1(b.0(x0))))) → A.1(b.0(a.0(a.0(a.0(x0)))))
A.0(a.0(a.0(a.1(b.0(x0))))) → A.0(b.0(a.0(a.0(a.0(x0)))))
b.1(b.0(a.1(b.0(x1)))) → a.0(a.0(a.0(x1)))
a.1(x0) → a.0(x0)
b.1(b.0(a.1(b.1(x1)))) → a.0(a.0(a.1(x1)))
a.0(a.0(a.0(x1))) → a.1(b.1(b.1(b.0(x1))))
b.1(x0) → b.0(x0)
a.0(a.0(a.1(x1))) → a.1(b.1(b.1(b.1(x1))))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ Narrowing
↳ QDP
↳ SemLabProof
↳ QDP
↳ DependencyGraphProof
↳ SemLabProof2
↳ QTRS Reverse
↳ QTRS Reverse
A.0(a.0(a.1(b.0(a.1(b.0(x0)))))) → A.0(b.1(b.0(a.0(a.0(a.0(x0))))))
A.0(a.0(a.0(a.1(b.1(x0))))) → A.0(b.0(a.0(a.0(a.1(x0)))))
A.0(a.0(a.1(b.0(a.1(b.0(x0)))))) → A.1(b.1(b.0(a.0(a.0(a.0(x0))))))
A.0(a.0(a.0(a.1(b.1(x0))))) → A.1(b.0(a.0(a.0(a.1(x0)))))
A.0(a.0(a.1(b.0(a.1(b.1(x0)))))) → A.1(b.1(b.0(a.0(a.0(a.1(x0))))))
A.0(a.0(a.1(b.0(a.1(b.1(x0)))))) → A.0(b.1(b.0(a.0(a.0(a.1(x0))))))
A.0(a.0(a.0(a.1(b.0(x0))))) → A.1(b.0(a.0(a.0(a.0(x0)))))
A.0(a.0(a.0(a.1(b.0(x0))))) → A.0(b.0(a.0(a.0(a.0(x0)))))
b.1(b.0(a.1(b.0(x1)))) → a.0(a.0(a.0(x1)))
a.1(x0) → a.0(x0)
b.1(b.0(a.1(b.1(x1)))) → a.0(a.0(a.1(x1)))
a.0(a.0(a.0(x1))) → a.1(b.1(b.1(b.0(x1))))
b.1(x0) → b.0(x0)
a.0(a.0(a.1(x1))) → a.1(b.1(b.1(b.1(x1))))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ Narrowing
↳ QDP
↳ SemLabProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ SemLabProof2
↳ QTRS Reverse
↳ QTRS Reverse
A.0(a.0(a.1(b.0(a.1(b.0(x0)))))) → A.0(b.1(b.0(a.0(a.0(a.0(x0))))))
A.0(a.0(a.1(b.0(a.1(b.1(x0)))))) → A.0(b.1(b.0(a.0(a.0(a.1(x0))))))
b.1(b.0(a.1(b.0(x1)))) → a.0(a.0(a.0(x1)))
a.1(x0) → a.0(x0)
b.1(b.0(a.1(b.1(x1)))) → a.0(a.0(a.1(x1)))
a.0(a.0(a.0(x1))) → a.1(b.1(b.1(b.0(x1))))
b.1(x0) → b.0(x0)
a.0(a.0(a.1(x1))) → a.1(b.1(b.1(b.1(x1))))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ Narrowing
↳ QDP
↳ SemLabProof
↳ SemLabProof2
↳ QDP
↳ QDPToSRSProof
↳ QTRS Reverse
↳ QTRS Reverse
A(a(a(b(a(b(x0)))))) → A(b(b(a(a(a(x0))))))
a(a(a(x1))) → a(b(b(b(x1))))
b(b(a(b(x1)))) → a(a(a(x1)))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ Narrowing
↳ QDP
↳ SemLabProof
↳ SemLabProof2
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ QTRS Reverse
a(a(a(x1))) → a(b(b(b(x1))))
b(b(a(b(x1)))) → a(a(a(x1)))
A(a(a(b(a(b(x0)))))) → A(b(b(a(a(a(x0))))))
a(a(a(x1))) → a(b(b(b(x1))))
b(b(a(b(x1)))) → a(a(a(x1)))
A(a(a(b(a(b(x0)))))) → A(b(b(a(a(a(x0))))))
a(a(a(x))) → b(b(b(a(x))))
b(a(b(b(x)))) → a(a(a(x)))
b(a(b(a(a(A(x)))))) → a(a(a(b(b(A(x))))))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ Narrowing
↳ QDP
↳ SemLabProof
↳ SemLabProof2
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QTRS Reverse
↳ QTRS Reverse
a(a(a(x))) → b(b(b(a(x))))
b(a(b(b(x)))) → a(a(a(x)))
b(a(b(a(a(A(x)))))) → a(a(a(b(b(A(x))))))
a(a(a(x))) → b(b(b(a(x))))
b(a(b(b(x)))) → a(a(a(x)))
b(a(b(a(a(A(x)))))) → a(a(a(b(b(A(x))))))
a(a(a(x))) → a(b(b(b(x))))
b(b(a(b(x)))) → a(a(a(x)))
A(a(a(b(a(b(x)))))) → A(b(b(a(a(a(x))))))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ Narrowing
↳ QDP
↳ SemLabProof
↳ SemLabProof2
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QTRS Reverse
↳ QTRS Reverse
a(a(a(x))) → a(b(b(b(x))))
b(b(a(b(x)))) → a(a(a(x)))
A(a(a(b(a(b(x)))))) → A(b(b(a(a(a(x))))))
a(a(a(x))) → b(b(b(a(x))))
b(a(b(b(x)))) → a(a(a(x)))
b(a(b(a(a(A(x)))))) → a(a(a(b(b(A(x))))))
a(a(a(x))) → a(b(b(b(x))))
b(b(a(b(x)))) → a(a(a(x)))
A(a(a(b(a(b(x)))))) → A(b(b(a(a(a(x))))))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ Narrowing
↳ QDP
↳ SemLabProof
↳ SemLabProof2
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ QTRS
↳ DependencyPairsProof
↳ QTRS Reverse
↳ QTRS Reverse
a(a(a(x))) → a(b(b(b(x))))
b(b(a(b(x)))) → a(a(a(x)))
A(a(a(b(a(b(x)))))) → A(b(b(a(a(a(x))))))
B(a(b(b(x)))) → A1(a(a(x)))
A1(a(a(x))) → B(a(x))
B(a(b(b(x)))) → A1(x)
B(a(b(b(x)))) → A1(a(x))
B(a(b(a(a(A(x)))))) → A1(a(b(b(A(x)))))
B(a(b(a(a(A(x)))))) → A1(a(a(b(b(A(x))))))
A1(a(a(x))) → B(b(a(x)))
A1(a(a(x))) → B(b(b(a(x))))
B(a(b(a(a(A(x)))))) → B(b(A(x)))
B(a(b(a(a(A(x)))))) → A1(b(b(A(x))))
B(a(b(a(a(A(x)))))) → B(A(x))
a(a(a(x))) → b(b(b(a(x))))
b(a(b(b(x)))) → a(a(a(x)))
b(a(b(a(a(A(x)))))) → a(a(a(b(b(A(x))))))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ Narrowing
↳ QDP
↳ SemLabProof
↳ SemLabProof2
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QTRS Reverse
↳ QTRS Reverse
B(a(b(b(x)))) → A1(a(a(x)))
A1(a(a(x))) → B(a(x))
B(a(b(b(x)))) → A1(x)
B(a(b(b(x)))) → A1(a(x))
B(a(b(a(a(A(x)))))) → A1(a(b(b(A(x)))))
B(a(b(a(a(A(x)))))) → A1(a(a(b(b(A(x))))))
A1(a(a(x))) → B(b(a(x)))
A1(a(a(x))) → B(b(b(a(x))))
B(a(b(a(a(A(x)))))) → B(b(A(x)))
B(a(b(a(a(A(x)))))) → A1(b(b(A(x))))
B(a(b(a(a(A(x)))))) → B(A(x))
a(a(a(x))) → b(b(b(a(x))))
b(a(b(b(x)))) → a(a(a(x)))
b(a(b(a(a(A(x)))))) → a(a(a(b(b(A(x))))))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ Narrowing
↳ QDP
↳ SemLabProof
↳ SemLabProof2
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ QDPOrderProof
↳ QTRS Reverse
↳ QTRS Reverse
A1(a(a(x))) → B(a(x))
B(a(b(b(x)))) → A1(a(a(x)))
B(a(b(b(x)))) → A1(x)
B(a(b(b(x)))) → A1(a(x))
B(a(b(a(a(A(x)))))) → A1(a(a(b(b(A(x))))))
A1(a(a(x))) → B(b(a(x)))
A1(a(a(x))) → B(b(b(a(x))))
a(a(a(x))) → b(b(b(a(x))))
b(a(b(b(x)))) → a(a(a(x)))
b(a(b(a(a(A(x)))))) → a(a(a(b(b(A(x))))))
The following pairs can be oriented strictly and are deleted.
The remaining pairs can at least be oriented weakly.
A1(a(a(x))) → B(a(x))
B(a(b(b(x)))) → A1(x)
B(a(b(b(x)))) → A1(a(x))
A1(a(a(x))) → B(b(a(x)))
Used ordering: Polynomial interpretation [25]:
B(a(b(b(x)))) → A1(a(a(x)))
B(a(b(a(a(A(x)))))) → A1(a(a(b(b(A(x))))))
A1(a(a(x))) → B(b(b(a(x))))
POL(A(x1)) = 0
POL(A1(x1)) = 1 + 2·x1
POL(B(x1)) = x1
POL(a(x1)) = 7 + 8·x1
POL(b(x1)) = 3 + 4·x1
b(a(b(a(a(A(x)))))) → a(a(a(b(b(A(x))))))
b(a(b(b(x)))) → a(a(a(x)))
a(a(a(x))) → b(b(b(a(x))))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ Narrowing
↳ QDP
↳ SemLabProof
↳ SemLabProof2
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ DependencyGraphProof
↳ QTRS Reverse
↳ QTRS Reverse
B(a(b(b(x)))) → A1(a(a(x)))
B(a(b(a(a(A(x)))))) → A1(a(a(b(b(A(x))))))
A1(a(a(x))) → B(b(b(a(x))))
a(a(a(x))) → b(b(b(a(x))))
b(a(b(b(x)))) → a(a(a(x)))
b(a(b(a(a(A(x)))))) → a(a(a(b(b(A(x))))))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ Narrowing
↳ QDP
↳ SemLabProof
↳ SemLabProof2
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QTRS Reverse
↳ QTRS Reverse
B(a(b(b(x)))) → A1(a(a(x)))
A1(a(a(x))) → B(b(b(a(x))))
a(a(a(x))) → b(b(b(a(x))))
b(a(b(b(x)))) → a(a(a(x)))
b(a(b(a(a(A(x)))))) → a(a(a(b(b(A(x))))))
A1(a(a(b(a(a(A(x0))))))) → B(b(a(a(a(b(b(A(x0))))))))
A1(a(a(b(b(x0))))) → B(b(a(a(a(x0)))))
A1(a(a(a(a(x0))))) → B(b(b(b(b(b(a(x0)))))))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ Narrowing
↳ QDP
↳ SemLabProof
↳ SemLabProof2
↳ QDP
↳ QDPToSRSProof
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ QTRS Reverse
↳ QTRS Reverse
B(a(b(b(x)))) → A1(a(a(x)))
A1(a(a(b(a(a(A(x0))))))) → B(b(a(a(a(b(b(A(x0))))))))
A1(a(a(b(b(x0))))) → B(b(a(a(a(x0)))))
A1(a(a(a(a(x0))))) → B(b(b(b(b(b(a(x0)))))))
a(a(a(x))) → b(b(b(a(x))))
b(a(b(b(x)))) → a(a(a(x)))
b(a(b(a(a(A(x)))))) → a(a(a(b(b(A(x))))))
a(a(a(x1))) → a(b(b(b(x1))))
b(b(a(b(x1)))) → a(a(a(x1)))
a(a(a(x))) → b(b(b(a(x))))
b(a(b(b(x)))) → a(a(a(x)))
↳ QTRS
↳ DependencyPairsProof
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
a(a(a(x))) → b(b(b(a(x))))
b(a(b(b(x)))) → a(a(a(x)))
a(a(a(x1))) → a(b(b(b(x1))))
b(b(a(b(x1)))) → a(a(a(x1)))
a(a(a(x))) → b(b(b(a(x))))
b(a(b(b(x)))) → a(a(a(x)))
↳ QTRS
↳ DependencyPairsProof
↳ QTRS Reverse
↳ QTRS Reverse
↳ QTRS
a(a(a(x))) → b(b(b(a(x))))
b(a(b(b(x)))) → a(a(a(x)))